CREC: Camera-based mobile robot for elderly care - Mohamad Jamatolail, Mohamed Fitri; Ambar, Radzi; Chew, Chang Choon; Abd Wahab, Mohd Helmy; Mohd, Mohd Norzali; Mhd Poad, Hazwaj; Abd Jamil, Muhammad Mahadi (WARSE, 2019)
Technologies that permits remote monitoring can be very helpful in reducing concerns of long-distance caregiving especially for elderly care. This work describes the design and development of a Camera-based mobile Robot for Elderly Care (CREC). A Pixy CMUcam5 camera is used as the main intermediary between the elderly and the movement of the robot. This camera uses a marker or tag to follow and monitor the elderly. Furthermore, a range finder sensor, Ultrasonic Sensor HC-SR04 is used as the main sensor to avoid obstacles as it is easy to inter-face and low-cost. An Arduino microprocessor is utilized to control the tyres of the mobile robot, so that the robot can follow the elderly with precision. In the current work, the robot is specifically designed to be used indoors. Several experiment have been carried out to show the usefulness of CREC. Experimental results demonstrated that CREC is capable to avoid obstacle and follow the marker tagged static and moving target successfully.